Neuronal intranuclear inclusion disease presenting with recurrent dizziness and headache: a case report with 5-year follow-up - Li, Limin; Luan, Xinghua; Liu, Kai; Wang, Chengzhe (Frontiers in Genetics, 2025)
Neuronal intranuclear inclusion disease (NIID) is a highly heterogeneous chronic neurodegenerative disease characterized by ataxia, extrapyramidal symptoms, peripheral neuropathy, autonomic nervous symptoms, and cognitive dysfunction. So far, recurrent dizziness and headache have been reported in cases of NIID. We report a case of a 71-year-old female patient with NIID, who was followed up for 5 years. The primary manifestations in this patient were episodic dizziness and headache, which are relatively nonspecific symptoms. Due to these characteristics, it is easy to misdiagnose or overlook the disease at the initial diagnosis. The patient exhibited characteristic high signal intensity at the corticomedullary junction on diffusion-weighted imaging (DWI) sequences of the head magnetic resonance imaging (MRI). We diagnosed NIID after detecting round, non-enveloped filamentous structures with a diameter of 1–2 μm within the nuclei of fibroblasts and Schwann cells and revealing 114 repeats of GGC amplification at the 5′end of the NOTCH2NLC gene. The findings of this case study indicate that patients presenting with atypical symptoms should be considered for this disease.